Stadt, Land, Berg. Vom Zusammenspiel von Dialektwahrnehmung und Topographie - Schwarz, Christian; Stöckle, Philipp (Linguistik Online, 2017)
In traditional dialectology, prominent geographical conditions are particularly made responsible for linguistic divergence between neighboring dialect areas (e. g. rivers, mountain ranges, etc.). Also modern national borders, territories of the Middle Ages or even older borders between tribal areas are made responsible as factors which consider linguistic areas as “mirror pictures of history” (Bach 1950: 31, translation: CS). Geographical as well as political borders seem to function as points of orientation that speakers use for constructing their cognitive surroundings and which consequently can result in linguistic divergence. In our contribution, we want to focus on the question of how the topographic nature of land-scapes influences the mental construction of linguistic areas by lay speakers. For pursuing this question, we will discuss results from German dialect areas that cover a broad range of different topographic landscape forms. The analyzed areas are located in the utter southwest of Germany (characterized by flat lands along the Rhine valley and low mountain ranges of the Black Forest) and in South Tyrol in the very north of Italy (characterized by mountains and deep valley cuttings). In our contribution, we will argue that speakers in their subjective dialect perception orient themselves toward national borders and topographically prominent points. With regard to topography primarily valleys are used as eponyms for subjective dialect areas.